1. x² - 6x + 9 = 0
D = 0
x = -b/2a = 6/2 = 3
Відповідь: в) 1
2. x² - 7x = -6
x² - 7x + 6 = 0
D = b² - 4ac = 49 - 24 = 25
√D = √25 = 5
x₁ = (-b + √D)/2a = (7 + 5)/2 = 12/2 = 6
x₂ = (-b - √D)/2a = (7 - 5)/2 = 2/2 = 1
x₁ + x₂ = 6 + 1 = 7
Відповідь: а) 7
3. x² - 7x + 6 = 0
x² - 7x + 6 = 0
D = b² - 4ac = 49 - 24 = 25
√D = √25 = 5
x₁ = (-b + √D)/2a = (7 + 5)/2 = 12/2 = 6
x₂ = (-b - √D)/2a = (7 - 5)/2 = 2/2 = 1
x₁ · x₂ = 6 · 1 = 6
Відповідь: г) 6
4. x² - 15x + 56 = 0
x² - 7x - 8x + 56 = 0
x(x - 7) - 8(x - 7) = 0
(x - 7)(x - 8) = 0
x - 7 = 0
x₁ = 7
x - 8 = 0
x₂ = 8
Відповідь: в) 7i 8
2 бр: 2х деталей
3 бр: 2х-70 деталей
Складаємо рівняння:
х+2х+2х-70=1085
5х-70=1085
5х= 1155
х=231 (1 бр.)
2*231=462 (2 бр.)
462-70=392 (3 бр.)